Philosophy of Islamic Education for Development Character Education Digital Era within Primary Education in Pangandaran Regency - Algifari, Djati Haidar; Sayuti, Ahmad; Fauzi, Asep Iqbal; Hamdani, Djaswidi Al; Rizal, Soni Samsu (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The rapid development of digital technology has fundamentally transformed the learning ecology of primary school aged children, thereby generating new challenges in the development of character education. This study aims to analyze how the philosophy of Islamic education, through the philosophical frameworks of ontology, epistemology, and axiology, can serve as both a conceptual and operational foundation for character education development in the digital era within primary education in Pangandaran Regency. The research employs a qualitative approach with an interpretive critical paradigm, utilizing philosophical inquiry alongside contextual empirical analysis that includes social data, educational policy documents, and relevant findings from previous studies. The findings indicate that digital character education should not be understood merely as the addition of media ethics content, but rather as an inherent component of the fundamental aims of Islamic education in cultivating morally grounded and dignified human beings. Ontologically, learners are positioned as moral subjects who must be guided to responsibly manage digital freedom. Epistemologically, character formation requires authentic experiences, habituation, and reflective processes within real digital contexts. Axiologically, the use of technology must be oriented toward public benefit (maṣlaḥah), the protection of human dignity, and the strengthening of learners’ agency. These findings suggest the necessity of developing a model of character education based on digital ta’dīb that integrates Islamic values, digital literacy, school culture, teachers’ exemplarity, and collaboration among families and communities. This model is considered relevant for addressing the challenges of character education in the digital era in a contextual and sustainable manner